EVALUASI PENERAPAN SISTEM AKUNTANSI PENGELUARAN KAS PENGGAJIAN PEGAWAI NEGERI SIPIL DI BADAN DIKLAT PROVINSI SULAWESI UTARA - Golose, Virginia Rebecka; Saerang, David P.E; Sabijono, Harijanto (Universitas Sam Ratulangi, 2014)
In the accounting system cash outlay necessary to procedure well and in accordance with established policy cash expenditures made outside the prescribed procedure, the possibility of fraud, theft, and embezzlement cash. So that can be said that the better expenditure accounting systems and procedures cash will be able to do it in the trust account the amount of cash in the financial statement. The problem in this study is how the implementation process payroll payments to the Civil Service Training Agency of North Sulawesi. The purpose of this study to evaluate the application of the accounting system cash expenditures, the payment of salaries of civil servants in the province of North Sulawesi training agency. This study is a descriptive research using qualitative methods in which an analysis is collecting, collating, and processing, in order to provide an overview of a particular state so that it can be deduced.Based on the results of the study indicate that the accounting. System is cash expenditure on Training Agency of North Sulawesi is generally well under Permendagri Number. 13 of 2006.